HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP KEJADIAN DIARE PADA BAYI USIA 6-12 BULAN DI PUSKESMAS DENPASAR BARAT II - P., Gede Odi Bayu D.; Duarsa, Dyah P.; Pinatih, Gde Ngurah I.; Ariastuti, Luh P. (JURNAL BIOMEDIK : JBM, 2020)
Abstract: Diarrhea is the leading cause of death and morbidity among infants in developing countries. This disease can be triggered by various factors, one of them is unprovided exclusive breastfeeding. Infants who were given exclusive breastfeeding until the age of 6 months had fewer digestive and growth problems. This study was aimed to determine the relationship between exclusive breastfeeding and the incidence of diarrhea among infants aged 6-12 months at West Denpasar II Public Health Center. This was an analytical study with a cross sectional design. Respondents were 84 mothers of infants selected by using purposive sampling technique. Data of this study were obtained by using the Likert scale questionnaire. The Pearson correlation test showed a negative correlation between exclusive breast feeding and the occurrence of diarrhea (r=-0.646 and p=0.000) and a positive correlation between partial breastfeeding and the occurrence of diarrhea (r=0.731 and p=0.000). In conclusion, there was a significant relationship between exclusive breastfeeding and the occurrence of diarrhea. The more the exclusive breast feeding the lower the occurrence of diarrhea. It is suggested to socialized the benefit of exclusive breastfeeding to nursing mother and mother to be, therefore, prevention of infant diarrhea can be achieved.Keywords: infants, diarrhea, exclusive breastfeeding Abstrak: Diare merupakan penyebab utama terjadinya mortalitas dan morbiditas pada bayi di negara berkembang. Diare dapat dipicu oleh berbagai faktor, salah satunya ialah tidak dilakukannya pemberian ASI eksklusif. Bayi yang diberikan ASI eksklusif sampai usia 6 bulan lebih sedikit mengalami gangguan gastrointestinal dan gangguan pertumbuhan. Penelitian ini bertujuan untuk mengetahui adanya hubungan antara pemberian ASI eksklusif dengan angka kejadian diare pada bayi usia 6-12 bulan di Puskesmas Denpasar Barat II. Jenis penelitian ialah analitik dengan desain potong lintang. Responden berjumlah 84 ibu dari bayi yang dipilih dengan teknik purposive sampling. Pengumpulan data yang digunakan ialah melalui kuesioner dengan skala Likert. Uji korelasi Pearson menunjukkan hubungan negatif antara pemberian ASI eksklusif dan kejadian diare (r=-0,646 dan p=0.000) serta hubungan positif antara pemberian ASI parsial dengan kejadian diare (r=0,731 dan p=0,000). Simpulan penelitian ini ialah terdapat hubungan bermakna antara pemberian ASI eksklusif dengan kejadian diare. Semakin meningkatnya pemberian ASI eksklusif maka kejadian diare akan menurun. Disarankan untuk meningkatkan sosialisasi masalah pemberian ASI eksklusif kepada ibu menyusui ataupun calon ibu menyusui agar dapat meningkatkan kesehatan bayi khususnya terhindar dari penyakit diare.Kata kunci: bayi, diare, pemberian asi eksklus